A canker disease of apple caused by Cytospora parasitica recorded in China. Issue 3 (9th February 2018) - Ma, R.; Liu, Y.‐M.; Yin, Y.‐X.; Tian, C.‐M.
Summary: A stem canker disease of apple that differs from previously reported canker diseases has been recorded in Xinjiang Uygur Autonomous Region in China. Eight Cytospora strains obtained from diseased apple trees and inoculated onto healthy apple tree branches resulted in the development of the same disease symptoms. This pathogen formed conceptacles, which were multilocular pycnidia with common walls and a single ostiole. Comprehensive analysis of three DNA sequence regions (internal transcribed spacer, large ribosomal subunit and transcription elongation factor) and morphological and cultural characteristics revealed that these strains were most similar to the fungus Cytospora parasitica . This is the first report of C. parasitica causing canker disease of apple in China.